Patient activation in older people with long-term conditions and multimorbidity: correlates and change in a cohort study in the United Kingdom. Issue 1 (December 2016) - Blakemore, Amy; Hann, Mark; Howells, Kelly; Panagioti, Maria; Sidaway, Mark; Reeves, David; Bower, Peter
Abstract Background Patient Activation is defined as the knowledge, skill, and confidence a patient has in managing their health. Higher levels of patient activation are associated with better self-management, better health outcomes, and lower healthcare costs. Understanding the drivers of patient activation can allow better tailoring of patient support and interventions. There are few data on patient activation in UK patients with long-term conditions. Methods A prospective cohort design was used. Questionnaires were mailed to 12, 989 patients over the age of 65 years with at least one long-term condition in Salford, UK. They completed the Patient Activation Measure and self-report measures of: depression, health literacy, social support, health-related quality of life, and impact of multimorbidity. We report descriptive data on baseline activation and change over time, and use multivariate regression to model associations with patient activation at baseline and predictors of change in Activation over 6 months. Results The cohort included 4377 (33.6 %) older people, of whom 4225 were mailed a further questionnaire at 6 months; 3390 returned it complete (80.2 %). At baseline, 15 % self-reported PAM level 1, 16 % level 2, 45 % level 3, and 25 % level 4. Across all patients, depression had the strongest association with patient activation. Other important factors were: older age, being retired, poor health literacy, health-related quality of life, and social support. Total number of self-reported comorbidities and the perceived impact of comorbidities were also important for patients with more than one long-term condition. Patient activation scores were reasonably enduring over time (r  = 0.43 between baseline and at six months), although nearly half changed 'levels' of activation over that time. Few variables predicted change in activation over 6 months. Conclusions This is the first large scale assessment of patient activation in the UK. Our data may be useful in identifying patients who need support with patient activation, and allow interventions (such as health coaching) to be tailored to better support older patients with long-term conditions who have symptoms of depression, poor social support and impaired health literacy. Further analyses of longitudinal studies will be necessary to better understand the causal relationships between patient activation and variables such as depression.